PROMOTION STRATEGY BY PALU CITY GOVERNMENT TO PULLING INVESTORS INTEREST IN PALU SPECIAL ECONOMIC ZONE - Muhammad Khairil (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
SEZ (Special Economic Zone) is one of the government's policy programs in national development planning. Reliable and excellent business and investment activities are the main objectives of the Special Economic Zone policy. Promotion strategy in attracting investors interest continue to be enhanced by Palu City Government. The purpose of this research is to know the efforts made by Palu City Government in pushing Palu Special Economic Zone to potential investors. The method used is qualitative method with case study approach. The results of this study indicate the interest to attract investors to do personal selling done by direct communication between the Government of Palu City and Central Sulawesi Provincial Government with potential investors. Finally constructed suggestions for the strategy of promotion of Special Economic Zones to attract potential investors to invest in Special Economic Zones.The contribution of this research is to provide insight on personal selling with potential investors done by the government of Palu and the Central Sulawesi province.